Social Behavior in the Working Relationship Between Ship Owners and Fishermen in Kupang City - Raimundus Nggajo; Tri Wiji Nurani; Darmawan; Iin Solihin; Zulkarnain; Nurani Khoerunnisa (International Journal of Marine Engineering Innovation and Research, 2026)
Indonesian fishing communities possess unique social characteristics due to their dependence on the sea as their primary source of livelihood. Despite abundant coastal and marine resources, fishers often remain trapped in cycles of structural poverty. The primary factors contributing to this include limited human resource quality, restricted access to technology, and limited market and capital control. Fishermen face low income due to challenges in employment relationships because the fishermen’s social dependence on ship owners, which results in unilateral control over market access and selling prices. Additionally, issues persist regarding competency enhancement, occupational safety, and facility support. This study aims to identify social behaviors that require intervention to improve social norms in the working relationships between ship owners and fishermen in Kupang City. Employing a soft systems methodology, the research identifies social issues necessitating intervention in the interaction patterns among fishermen, ship owners, and other stakeholders. The study yields three root definitions. First, local governments, fishing ports, along with ship owners are creating a competency improvement program for fishermen, through the implementation of independent training to achieve enhanced skills, workplace safety, and professionalism of fisheries human resources. Second, the local government, ship owners and fishermen's organizations, established a mediation and labor relations management system through a fair profit-sharing mechanism and clear work regulations. Third, local governments, fishermen's organizations and related institutions, are designing a system of protection and independence for fishermen through strengthening market access, financial management, and alternative livelihoods, to improve welfare and reduce vulnerability.